Evaluation of the provision of enteral nutrition in critically ill patients receiving mechanical ventilation - Mayasari, Meike; Mahmudah, Fella Farikhatul; Perwitasari, Silviana; Rahayu, Umi (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2023)
ABSTRACTBackground: Providing enteral nutrition to ICU patients is often challenging, leading to sufficient enteral nutrition that is hardly achieved. This condition is caused by gastrointestinal motility disorder and other complications that often happen during enteral nutrition provision. Therefore, it is important to understand the level of nutritional support and the challenges in the form of interruption during enteral nutrition to critically ill patients receiving mechanical ventilation to optimise the benefit of nutritional support for patients, including reducing the duration of hospitalisation and mortality.Objectives: This study aims to evaluate the provision of enteral nutrition and identify the cause of interruption for patients with mechanical ventilation in one of the tertiary hospitals in Yogyakarta, Indonesia who receive enteral nutrition.Methods: This is a cross-sectional study. The subject of the study is patients who fulfil the inclusion and exclusion criteria. Inclusion criteria include patients who were in ICU for ≥72 hours, receiving mechanical ventilation. While the exclusion criteria include patients with contraindications for enteral nutrition such as unstable haemodynamic, bowel obstruction, persistent severe ileus, gastrointestinal bleeding, nasogastric tube (NGT) placement is not possible, patients receiving oral nutrition with non-invasive ventilation, patients with feeding tube before admission, or patients from other ICU or HCU.Results: Patients needed, on average, 13 hours to receive initial enteral nutrition (SD ± 9.89 hours), with a period between 0 – 50 hours since admission to ICU. The mean time for patients to receive full feeding is 4 days ± 2.4 days. On the other hand, 16 out of 75 patients (21.2%) did not reach the targeted intake during admission. The cause of the interruption of enteral nutrition includes gastric residual volume (GRV), percutaneous dilatation tracheostomy (PDT) procedure, vomiting, bloating, surgery, CT scan, etc.Conclusion: Many causes of interruption and inadequate intake of enteral nutrition can be prevented. The absence of protocol agreed upon by the patient care team could be one of the influencing factors.KEYWORD:  enteral nutrition; enteral nutrition interruption; mechanical ventilation